2011
DOI: 10.1590/s1135-57272011000400002
|View full text |Cite
|
Sign up to set email alerts
|

Prevalencia, grado de control y tratamiento de la hipertensión arterial en la población de 30 a 74 años de la Comunidad de Madrid: Estudio PREDIMERC

Abstract: Our data on prevalence, treatment and control are at the lower-intermediate between those reported in previous studies on Spanish and European populations. However, the HA is a public health problem in the CM. Many hypertensive patients are not detected. Of those detected, only 1 in 3 of men and 1 in 2 women are well controlled.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0
3

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 25 publications
2
3
0
3
Order By: Relevance
“…Being a woman is associated with up to 14% lower risk in the SWZ (worse socioeconomic level). This is consistent with the findings from other works in the Spanish context, 32 36 which imply the need to seek more effective actions to control hypertension in men, grounded on studies that identify the factors leading to poor hypertension control in men.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Being a woman is associated with up to 14% lower risk in the SWZ (worse socioeconomic level). This is consistent with the findings from other works in the Spanish context, 32 36 which imply the need to seek more effective actions to control hypertension in men, grounded on studies that identify the factors leading to poor hypertension control in men.…”
Section: Discussionsupporting
confidence: 91%
“…Prior studies have shown poorer degrees of control than in this work; it must be underlined that in these studies the general population is analysed and samples also include people with HBP who had not been diagnosed before and therefore had not been monitored. 31 32 …”
Section: Discussionmentioning
confidence: 99%
“…Our investigation revealed a high prevalence of AHT in the Spanish population, reaching almost 30% of participants over 30 years of age. Similar results appear repeatedly in publications on the epidemiology of this pathology in Spain [43][44][45] and in other developed countries [46]. However, the alarming magnitude of this problem is not exclusively limited to the frequency of the appearance of this syndrome but, among other aspects, the high regularity with which the disorder remains undetected or simply is not pharmacologically treated.…”
Section: Discussionsupporting
confidence: 83%
“…Prior nationwide studies described more favorable ratios in the use of pharmacotherapy [44,47], probably explained by the consideration of a higher threshold for the detection of AHT. However, in any case it is fitting to mention that a slight reduction in pharmacological infra-management of AHT has been experienced over the last decade [45], favored by a greater familiarity with and consciousness of the problem within the healthcare sector, a result of, among other aspects, new health policies implemented in developed countries, and the greater evidence of clinical efficacy of the active ingredients available [7]. However, the figures obtained are still far from the desired results depending upon different approaches to ATH treatment [48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…Con respecto a la reducción de los niveles de presión arterial se pudo mostrar que hasta un 17% de la hipertensión en los hombres y un 15% en las mujeres podría ser controlada si se reduce, al máximo, el desconocimiento y se inicia una intervención para problemas con el alcohol (véase los resultados del análisis de sensibilidad 2). En dicho escenario, las diferencias actuales entre hombres y mujeres también desaparecerían (para evaluaciones recientes sobre diferencias de sexo en España véase Gijón-Conde y Banegas, 2012;Ortiz Marrón et al, 2011).…”
Section: Discussionunclassified